Pengetahuan Spiritual Yoga - I Nyoman Dayuh (UHN IGB Sugriwa Denpasar, 2015)
The education paradigm emhasizes the complete balance of intelectual, emotional, and spiritual potencies. The spiritual one becomes more important when the influence of materialism, hedonism, and pragmatism have becoming significant. To face it self-control as taught in Yogasutra Patanjali is crucial.